Using video and online subtitling to communicate across languages from West Papua. (1st June 2014) - Crosby, Alexandra; Notley, Tanya
<x xml:space="preserve">Abstract</x> In this paper we examine mediated practices and experiences of online translation and subtitling. Our paper is based on a collaboration with EngageMedia − a not‐for‐profit organisation based in Australia and Indonesia − and is specifically focused on its work in West Papua. We argue that the video‐hosting and online subtitling that is enabled through EngageMedia's websites, while mobilising West Papuan stories in a logical, relatively fast and organised manner, is embedded in a more messy socially‐mediated translation process that occurs across shifting scales (local, national, regional, and global), and a range of cultures (online, offline, local, global, networked). By examining this socially‐mediated process we identify the many ways in which 'friction' emerges and we conclude that for video to support multi‐lingual, translational communication and activism, social and technological infrastructures need to be further developed to avoid 'restrictive frictions' and create 'productive' ones.